PENGARUH SUHU RUANGAN DAN KECEPATAN NIP ROLL TERHADAP KETEBALAN FILM PLASTIK HDPE - Nastiti Afiati; Arief Krisna Wibowo; Muh. Wahyu Syabani (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2020)
HDPE-based plastic bag products are processed using a blown film extrusion machine. Problems that often occur during processing are the instability of plastic bubbles and the difference in thickness of the plastic sheet. The purpose of this paper is to determine the effect of room temperature on bubble instability defects to predict engine temperature settings. In addition, it provides a solution to overcome thickness difference defects caused by inappropriate nip roll speeds. Each defect problem was predicted using a polynomial trendline graph. The results show that the higher the room temperature, the unstable bubbles and vice versa. In order for the engine temperature to remain stable, the application of parameter settings according to room temperature can be carried out by looking at the room temperature trend. Furthermore, to keep the room temperature stable, the company needs to install an exhaust fan. While the results of observations and trend data on thickness difference defects obtained the optimal nip roll speed is 37.25-37.65 Hz for a thickness of 0.08-0.12 mm. The faster the nip roll, the less thickness it will be.